PERSYARATAN DALAM PENENTUAN HAK ASUH - Ida Kurnia; Alexander Sutomo; Cliff Geraldio (Jurnal Bakti Masyarakat Indonesia, 2022)
Marriage is an important event in human life. The purpose of marriage is to have children and live happily. However, it is not uncommon for marriages to end in divorce. Divorce that occurs in the household will eventually win custody of the child. In determining custody, the judge gives a verdict on who is more worthy to take care of the child, namely who is considered more entitled and more capable. In the court's decision with custody cases with various conditions in the family, the court's decision prioritizes child custody to the mother, noting that the child is still under 12 years old and the mother does not experience psychological disorders. The child custody decision can also fall to the father if the mother has shortcomings such as mental disabilities or other things related to psychological. Custody of the child can be separated from both parents if the parent is not able to take care of, educate, and care for the child. Bad habits of the child's parents can eliminate custody of the child from him. Law No. 35 of 2014 on child protection regulates all matters related to children with the main purpose of maintaining the rights of the child. The rights of a child have arisen from the time he is in the womb until he is an adult and is considered not a child anymore if he has entered into the marriage in accordance with the Civil Code and marriage law. Children should be taken care of, educated, well cared for, and given knowledge to be able to support their future better because children are the next generation of the nation ABSTRAK; Perkawinan merupakan peristiwa penting dalam hidup manusia. Tujuan dari perkawinan salah satunya memiliki anak dan hidup bahagia. Namun tidak jarang perkawinan dapat berakhir dengan perceraian. Perceraian yang terjadi dalam rumah tangga pada akhirnya akan merebutkan hak asuh atas anak. Dalam penentuan hak asuh hakim memberikan putusan siapa yang lebih layak untuk mengurus anak, yaitu siapa yang dianggap lebih berhak dan lebih mampu. Dalam putusan pengadilan dengan perkara hak asuh dengan berbagai macam kondisi dalam keluarga, putusan pengadilan lebih mengutamakan hak asuh anak jatuh kepada ibunya, dengan catatan apabila anak tersebut masih dibawah 12 tahun dan sang ibu tidak menggalami gangguan dalam psikologis. Putusan hak asuh anak juga dapat jatuh kepada sang ayah apabila sang ibu memiliki kekurangan seperti cacat mental atau hal-hal lain yang berkaitan dengan psikologis. Hak asuh anak dapat lepas dari kedua orang tuanya apabila orang tua tersebut tidak mampu mengurus, mendidik, serta mengasuh anaknya. Kebiasaan buruk dari orang tua sang anak dapat menghilangkan hak asuh atas anak dari dirinya. Undang-undangÂ  No. 35 tahun 2014 tentang perlindungan anak mengatur segala hal yang berkaitan dengan anak dengan tujuan utama menjaga hak dari sang anak. Hak seorang anak sudah timbul sejak ada di dalam kandungan sampai ia dewasa dan di anggap bukan anak-anak lagi apabila ia telah mengsungkan perkawinan hal ini sesuai dengan Kitab Undang-undang Hukum Perdata dan Undang-undang Perkawinan. Anak semestinya dijaga, dididik , dirawat dengan baik, serta diberi pengetahuan agar mampu menunjang masa depannya lebih baik karena anak merupakan generasi penerus bangsa